Weaving the world of the ancestors: Early incised stones from the Kincaid Shelter in west Central Texas. (2nd January 2016) - Mock, Shirley Boteler
Abstract : Incised stones recovered from the Kincaid Shelter in west Central Texas are the focus of inquiry in this paper. Despite the inherent problems in interpretation of the portable forms, I utilize multiple lines of information gathered from diverse sources to inform the ideas presented here. I provide detailed evidence to support my conclusion that the imagery incised on the stones depicts weaving techniques (twining, plaiting, cordage motifs, and netting). The additional presence of an incised orb spider web on some stones echoes its metaphoric relationship to weaving and the female spider's role in the myths and legends of North America. The context of the incised stones in the Kincaid rock shelter provides support for a plausible explanation that women, typically the producers of woven items such as baskets and mats in many North American cultures, were the creators of the Kincaid incised stones. I discuss the difficulty in discovering meaning across time and place and propose that the incised imagery was not an end product in itself. Rather it represents a visual dialog to stimulate recall and evocation of ancestral stories or myths to expand, explore, or reinforce the well-being of the Kincaid people in some way.